2024
DOI: 10.1039/d4dt00149d
|View full text |Cite
|
Sign up to set email alerts
|

Neutral rhenium(i) tricarbonyl complexes with sulfur-donor ligands: anti-proliferative activity and cellular localization

Aviva Levina,
Kartika Wardhani,
Liam J. Stephens
et al.

Abstract: Rhenium(I) tricarbonyl complexes are widely studied for their cell imaging properties and anti-cancer and anti-microbial activities, but the complexes with S-donor ligands remain relatively unexplored. A series of six fac-[Re(CO)3(NN)(SR)]...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 81 publications
(200 reference statements)
0
1
0
Order By: Relevance
“…These novel phosphorescent stains offer a simple, quick, reproducible, and precise flow-cytometry-based method of direct staining of intact EVs, which has outstanding potential for studies of the interactions and communication between EVs and target cells to be reported elsewhere. This concept opens up unprecedented opportunities to conduct experiments that explore various metal complexes [ 53 ] as selective stains of intact EVs from numerous cell types.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…These novel phosphorescent stains offer a simple, quick, reproducible, and precise flow-cytometry-based method of direct staining of intact EVs, which has outstanding potential for studies of the interactions and communication between EVs and target cells to be reported elsewhere. This concept opens up unprecedented opportunities to conduct experiments that explore various metal complexes [ 53 ] as selective stains of intact EVs from numerous cell types.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%